Investigasi Behavioral Intention pada Sistem Pembayaran QRIS di Merchant UMKM - Bobby Setiawan; Marwah Khairani; Tadila Fadil; Tengku Mohd. Khairal Abdullah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In this era of digitalization, technological developments are growing rapidly. One form of development is the emergence of the convenience of non-cash transactions such as payments using cards and mobile payments at MSME merchants or micro, small and medium enterprises. Bank Indonesia as the payment system regulator in Indonesia in collaboration with other institutions launched QRIS as a new payment system. This study aims to increase the number of payment transactions and simultaneously increase the profitability of PJSP by identifying changes in behavioral intentions on several independent variables including Social Influence, Perceived Usefulness, Perceived Ease of Use, and Attitude Toward Behavior Intention. Then Perceived Usefulness of Behavior Intention with Attitude Toward as a mediation of Behavior Intention. The results of the research conducted are that there are research variables that are influential and not influential. Perceived usefulness affects attitude towards to use of the QRIS Payment System, and attitude towards using QRIS (full mediating) but does not affect behavioral intention. Perceived ease of use affects attitude towards using QRIS Payment System, and attitude towards using QRIS (full mediating) but does not affect behavioral intention. Attitude towards using QRIS Payment System affects behavioral intention. And Social influence is influenced by behavioral intention and not influenced by attitude towards using QRIS Payment System.